Development of students' communicative culture in the context of artistic practices - Derkach, Svitlana; Melnyk, Myroslava; Fisher, Volodymyr; Krypchuk, Mykola; Chystiakov, Oleh (Linguistics and Culture Review, 2021)
The relevance of the research is conditioned upon the problem of developing a communicative culture among students, considering the influence of the artistic component, both its professional part and the social one, explained by the introduction of the presented artistic image into the life of the younger generation. The purpose of the article is to develop a model for the development of communicative culture among students. The leading method to investigate this problem is the B.I. Dodonov method, studying the emotional, motivational component of the personality, considering the emerging emotional background as a value on which the health and quality of life of a person depend. Depending on being in a certain artistic component, an individual has various experiences at the psycho-emotional level, which form a motivational environment for perceiving the world and the course of personal actions based on getting into various life situations. This model, based on artistic practices, creates conditions for the holistic development of the individual, aimed at preserving psychological and physical health, both personal and others, which is of practical importance for the education and well-being of society.